Comparison of radiographic and tomographic evaluations for measurement of the Canal Flare Index in dogs - Andrade, C.r. [UNESP]; Minto, B.w. [UNESP]; Dreibi, R.m. [UNESP]; Diogo, L.m.i. [UNESP]; Rocha, T.a.s.s.; Kawamoto, F.y.k.; Franco, G.g.; Uscategui, R.a.r.; Dias, L.g.g.g. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2021)
The outcome of total hip arthroplasty (THA) in dogs is directly related to surgical planning. Templating of radiographs prior to THA should help the surgeon anticipate prosthesis size and femoral shape allowing canal fill of the proximal metaphysis by the implant ensuring primary stable fixation. The canal flare index (CFI) obtained from radiograph has been used as a measure of risk of complications for the technique in human beings and dogs. However, standard radiographs only provide limited data for the selection of cementless prostheses and the assessment of their fit within the femoral canal, due to factors like radiographic magnification and femoral rotation. Therefore, three-dimensional evaluation based on computed tomography (CT) may be a better tool for CFI measurement. The aim of this study was to compare anatomical measurement with CFI values obtained from craniocaudal radiography and CT. Craniocaudal radiographs using a horizontal radiographic beam (CR), CT, and anatomical macroscopic measurements (A) were obtained from 45 femurs from 23 canine cadavers. The differences between the values of CFI obtained from radiograph (CFI-R), computed tomography on transverse (CFI- TT) and longitudinal axis (CFI-TL) compared to the CFI obtained from macroscopic measurements - gold standard - (CFI-A), and 95% limits of agreement (LOA) between the values, were evaluated by the Bland-Altman method. Dimensions obtained from CT techniques had a greatest mean difference from anatomical and CFI values were also different (P=0.032). Under the experimental conditions, the craniocaudal radiograph, provided the most accurate measurement of the CFI (mean difference: 0.087 ± 0.42).

O resultado da artroplastia total do quadril (ATQ) em cães está diretamente relacionado ao planejamento cirúrgico. O templating radiográfico pré-operatório da ATQ deve ajudar o cirurgião a prever o tamanho da prótese e o formato do fêmur, o que permitirá um preenchimento ideal da metáfise proximal pelo implante, garantindo, assim, fixação primária estável. O índice de alargamento do canal (Canal Flare Index - CFI) obtido em radiografias tem sido utilizado como fator de risco de complicações para a técnica em humanos e cães. No entanto, as radiografias podem fornecer apenas dados limitados para a seleção de próteses não cimentadas e a avaliação do seu encaixe no canal femoral, devido a fatores como ampliação radiográfica e rotação femoral. Portanto, a avaliação tridimensional baseada na tomografia computadorizada (TC) pode ser uma ferramenta vantajosa para a mensuração do CFI. O objetivo deste estudo foi comparar a medida anatômica com os valores de CFI obtidos na radiografia craniocaudal e na TC. Radiografias craniocaudais utilizando feixe radiográfico horizontal (CR), tomografia computadorizada e medidas macroscópicas anatômicas (A) foram obtidas de 45 fêmures de 23 cadáveres caninos. As diferenças entre os valores de CFI obtidos na radiografia (CFI-R), na tomografia computadorizada no eixo transversal (CFI-TT) e no eixo longitudinal (CFI-TL), em comparação com os valores de CFI obtidos nas medições macroscópicas - padrão-ouro - (CFI-A) e os limites de concordância de 95% (LOA) entre os valores, foram avaliadas pelo método de Bland-Altman. As dimensões obtidas pelas técnicas de TC apresentaram maior diferença média dos valores anatômicos, e as do CFI também foram diferentes (P=0,032). Nas condições experimentais, a radiografia craniocaudal forneceu a medida mais precisa do CFI (diferença média: 0,087 ± 0,42) para representar o padrão-ouro deste estudo.
[Comparação entre avaliação radiográfica e tomográfica para mensuração do Canal Flare Index em cães]
Keywords: computed tomography; craniocaudal projection; cementless THR; femoral morphology; three-dimensional analysis; tomografia computadorizada; projeção craniocaudal; morfologia femoral; análise tridimensional; substituição total de quadril não cimentada